2021
DOI: 10.7717/peerj.10967
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plastic film mulch with biochar application on crop yield, evapotranspiration, and water use efficiency in northern China: A meta-analysis

Abstract: Background China is the leading consumer of plastic film worldwide. Plastic film mulched ridge-furrow is one of the most widely adopted agronomic and field management practices in rain-fed agriculture in dry-land areas of China. The efficiency of plastic film mulching as a viable method to decrease evapotranspiration (ET), increase crop yields, and water use efficiency (WUE), has been demonstrated extensively by earlier studies. Methods A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 86 publications
(54 reference statements)
1
8
0
Order By: Relevance
“…Biochar improved the annual cumulative mean of NFY (8%) and AFY (11%) as compared to no-biochar in this study (Please, refer to Table 2 ). These outcomes are in line with Mak-Mensah et al (2021) , who reported combined application of biodegradable film with biochar in the Loess Plateau of China increased yield by 22.86% compared with FP. This was corroborated by Liu et al (2014) who achieved a higher yield of sweet potato (53.77%; p < 0.05), with biochar amendment than with no biochar treatment (control).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Biochar improved the annual cumulative mean of NFY (8%) and AFY (11%) as compared to no-biochar in this study (Please, refer to Table 2 ). These outcomes are in line with Mak-Mensah et al (2021) , who reported combined application of biodegradable film with biochar in the Loess Plateau of China increased yield by 22.86% compared with FP. This was corroborated by Liu et al (2014) who achieved a higher yield of sweet potato (53.77%; p < 0.05), with biochar amendment than with no biochar treatment (control).…”
Section: Discussionsupporting
confidence: 89%
“…This may be an ideal agronomic practice for smallholder farmers to increase yield in crop production. The practice could also be used as a soil and water conservation strategy in rain-fed agriculture, especially in climate-changing areas to reduce drought impact while decreasing runoff and erosion ( Mak-Mensah et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Peer-reviewed papers published in English between 2000 and 2020 that investigated the effects of tied-ridge-furrow with or without mulching or fertilizer on field crops were retrieved from online databases (ISI Web of Science, PubMed, Google Scholar, Scopus (Elsevier), JSTOR, and Science Direct) as previously described in Mak-Mensah et al (2021). More than one database was used to minimize selection bias.…”
Section: Scope Of Peer-reviewed Papersmentioning
confidence: 99%
“…Meta-analysis, fundamentally the 'analysis of analyses', is a method of quantitatively (a) recognizing overviews from a range of separate and disparate studies, and (b) determining inadequacies in existing research such that new preferences for future research can be proposed (Kuznetsov, Passot & Sulem, 2008). Meta-analysis allows for statistical analysis of effect sizes and objective evaluation of other authors' experimental results (Mak-Mensah et al, 2021). Meta-analysis increases the statistical potential for evaluating theories and comparing treatment differences in various contexts (Luo, Wang & Sun, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Meta-analysis, fundamentally the 'analysis of analyses', is a method of quantitatively (a) recognizing overviews from a range of separate and disparate studies, and (b) determining inadequacies in existing research such that new preferences for future research can be proposed (Kuznetsov et al, 2008). Meta-analysis allows for statistical analysis of effect sizes and objective evaluation of other authors' experimental results (Mak-Mensah et al, 2021). Meta-analysis increases the statistical potential for evaluating theories and comparing treatment differences in various contexts (Luo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%